GENERAL PHYSICAL PREPARATION OF FREESTYLE WRESTLERS - Khanturayev, Nodir (Журнал иностранных языков и лингвистики, 2022)
To achieve high sports results, the level of physical preparation of a wrestler as well as the development of physical qualities: flexibility, speed, strength, agility and endurance are of paramount importance. Therefore, the process of physical preparation, which is carried out in conjunction with the process of enhancing wrestling techniques, plays a key role in Freestyle wrestling. Lack of technique poses trauma and wound, so it needs to be corrected as soon as possible so as for the athlete to be prepared for training or competition. It is also significant to examine the physical fitness levels required for the training schedule and competition. Wrestlers should have the right fitness levels (both health and skill related components ought to be considered) for Freestyle wrestling and their performance. This article elucidates the exercises used to uplift the physical preparation of freestyle wrestlers, which are used particularly in the development of general and specific physical preparation.